If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + ln(x + -3) = ln(10) Multiply ln * x lnx + ln(x + -3) = ln(10) Reorder the terms: lnx + ln(-3 + x) = ln(10) lnx + (-3 * ln + x * ln) = ln(10) lnx + (-3ln + lnx) = ln(10) Reorder the terms: -3ln + lnx + lnx = ln(10) Combine like terms: lnx + lnx = 2lnx -3ln + 2lnx = ln(10) Reorder the terms for easier multiplication: -3ln + 2lnx = 10ln Solving -3ln + 2lnx = 10ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-10ln' to each side of the equation. -3ln + -10ln + 2lnx = 10ln + -10ln Combine like terms: -3ln + -10ln = -13ln -13ln + 2lnx = 10ln + -10ln Combine like terms: 10ln + -10ln = 0 -13ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-13 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-13 + 2x)' equal to zero and attempt to solve: Simplifying -13 + 2x = 0 Solving -13 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 2x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 2x = 0 + 13 2x = 0 + 13 Combine like terms: 0 + 13 = 13 2x = 13 Add '-2x' to each side of the equation. 2x + -2x = 13 + -2x Combine like terms: 2x + -2x = 0 0 = 13 + -2x Simplifying 0 = 13 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9x^2+30x=29 | | 54=w/3 | | (y^2+2)(5y+7)= | | 6x-2=.02 | | 2x+3x+13=90 | | 0.5(x-1)=2(x+5) | | w-4w= | | F(x)=9x-13 | | 3(5+3x)-2=23 | | 10y+10-3y=-11 | | -3x+9=4x+12 | | 4(p+6q-10)= | | 5r^3-10r^2=0 | | -16t^2+100t+5=0 | | C+(61)=-97 | | 40x+15y=505 | | (-a^2+1)-(a^2-2)+(5a^2-4a+8)= | | 100x=20 | | r/4-10=-6 | | sqrt(2−3x)/sqrt(5x)=3 | | 2x+12x+8=15 | | 4t^2+12t=12 | | 3/4-x/2=3/8 | | y=.6x-3 | | C+(-16)=-97 | | 3y/2 | | 12x+4=3x+22 | | -7(6y)= | | 3y/2=1200/y | | 3x^2-y^2=2 | | x=1+x+1 | | 17+3x=-5-1x |